2011
DOI: 10.17796/jcpd.36.1.e25411r576362262
|View full text |Cite
|
Sign up to set email alerts
|

Association between Caries, Obesity and Insulin Resistance in Mexican Adolescents

Abstract: Aim: To determine the association among dental caries, obesity and insulin resistance in Mexican adolescents.Methods: Body Mass Index, obesity (OB) blood pressure, insulin level, insulin resistance (IR), triglycerides level, serum HDL-cholesterol (cHDL), DMFT index and salivary flow were measured. Results:Anthropometric measures showed a significant statistical difference (p < 0.05). Insulin level was 8.98 for healthy subjects, whereas for OB-IR group was 25.35, there was a statistical significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 16 publications
1
34
0
4
Order By: Relevance
“…Willershausen et al (2004) were able to establish a significant association between increased tooth decay and overweight in both permanent and temporary teeth. Similar results were obtained in studies conducted in Sweden (Larsson et al, 1995;Göthe Mundt, 2003) and preschoolers in Mexico (Vázquez-Nava et al, 2010;Loyola-Rodriguez et al, 2011).…”
Section: Introductionsupporting
confidence: 87%
“…Willershausen et al (2004) were able to establish a significant association between increased tooth decay and overweight in both permanent and temporary teeth. Similar results were obtained in studies conducted in Sweden (Larsson et al, 1995;Göthe Mundt, 2003) and preschoolers in Mexico (Vázquez-Nava et al, 2010;Loyola-Rodriguez et al, 2011).…”
Section: Introductionsupporting
confidence: 87%
“…As a result, association between caries and obesity has long been suspected. [678910] However, findings of obesity–caries relationship in children from different countries have actually been mixed and inconclusive. Conclusions on positive links, no links, and inverse links are all present.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports described the link between caries and weight, indicating that obese children had more caries than children in the normal-weight group. [678910] However, others concluded that there was no significant difference in the DMFT/dmft score among different body mass index (BMI) groups in 3–8-year-old children. [11] Therefore, no consensus has been reached on the relationship between obesity and dental caries in children.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Segundo levantamentos realizados em países desenvolvidos, há um elevado percentual de profissionais que utilizam esses cimentos odontológicos em procedimentos que vão desde os preventivos, passando por procedimentos curativos tradicionais (como restaurações, bases e forramento de cavidades) até como agentes de cimentação em tratamentos ortodônticos e protéticos.…”
Section: Introductionunclassified
“…Dessa maneira, o cimento obtido é constituído de partículas vítreas revestidas por camada de sílica gel presentes em uma matriz formada pelos sais de poliacrilato de cálcio e de alumínio. [5][6][7] Em recente artigo, foi demonstrada a preparação e caracterização de um cimento odontológico obtido a partir do sistema vítreo SiO 2 -Al 2 O 3 -CaO preparado por método químico, 9 considerando que a inclusão de fluoreto na formulação do pó do vidro precursor dos CIV é importante nas aplicações odontológicas, pois os íons fluoreto liberados por esses cimentos aumentam a resistência contra cáries secundárias. Dessa forma, esse novo artigo reporta a síntese por método químico e a caracterização estrutural por ressonância magnética nuclear (RMN) e infravermelho (FTIR), de um pó experimental baseado no sistema vítreo SiO 2 -Al 2 O 3 -CaO -CaF 2 visando aplicações como precursores de cimentos odontológicos.…”
Section: Introductionunclassified